Measuring Pb isotope ratios in fresh snow filtrate refines the apportioning of contaminant sources in the Arctic - Astray, Blanca; Šípková, Adéla; Baragaño, Diego; Pechar, Jan; Krejci, Radovan; Komárek, Michael; Chrastný, Vladislav (Environmental pollution (1987), 2024)
The remoteness and low population in the Arctic allow us to study global environmental processes, where the analysis of indicators can provide useful information about local and distant pollution sources. Fresh snow represents a convenient indicator of regional and transboundary atmospheric contamination sources, entrapping aerosols, and particulates like a natural autosampler of the environment. Lead stable isotopes are widely used to trace and monitor local and distant pollution sources. However, the behavior of Pb within different snow components is still not thoroughly studied, and its significance could be underestimated if only larger particulates are accounted for. We collected snow and samples from potential sources (fuel, rocks, coal) in three Arctic localities: Nuuk (Greenland), Reykjavik (Iceland), and Longyearbyen (Svalbard). We separated the filtrate from the filter residue through 0.45 μm nitrocellulose membranes to isolate the low-diameter particles associated with long-range transport from larger particles of mostly local natural origin. Filtrates yielded higher EFs (enrichment factor as the Pb/Al ratio relative to the upper crust) than filtration residues (80 ± 104 and 2.1 ± 1.1, respectively), and Pb isotope signals similar to fuel and coal (206Pb/207Pb are 1.199 ± 0.028 in coal, 1.168 ± 0.029 in filtrates, 1.163 ± 0.013 in fuel, 1.137 ± 0.045 in residues, and 0.985 ± 0.020 in rocks). In contrast to filtrates, the filter residues present wider ranges of Pb isotope compositions and crustal contributions and lower EFs, so we suggest that filtrate contains Pb from fuel combustion more selectively, while the residue carries a more considerable contribution of local mineral dust that can mask the contribution of other anthropogenic or distant natural sources. These findings add weight to the notion that filtrates are a more selective measure of metal deposition from long-range anthropogenic emissions compared to analyzing bulk melted snow or only filter residues.
Keywords: Isotopes; monitorování životního prostředí; Lead; Snow; Coal; znečištění životního prostředí; Environmental Pollution; olovo; sníh; prach; uhlí; Dust; Environmental Monitoring; izotopy